2017
DOI: 10.18632/aging.101240
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse colonies of human skin fibroblasts in relation to cellular senescence and proliferation

Abstract: Development of personalized skin treatment in medicine and skin care may benefit from simple and accurate evaluation of the fraction of senescent skin fibroblasts that lost their proliferative capacity. We examined whether enriched analysis of colonies formed by primary human skin fibroblasts, a simple and widely available cellular assay, could reveal correlations with the fraction of senescent cells in heterogenic cell population. We measured fractions of senescence associated β-galactosidase (SA-βgal) positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…6A ) to evaluate a possible influence of the IR exposure on senescence in the progeny of irradiated cells. This enzyme is commonly used as a marker of cellular senescence since its expression is substantially elevated in senescent cells [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6A ) to evaluate a possible influence of the IR exposure on senescence in the progeny of irradiated cells. This enzyme is commonly used as a marker of cellular senescence since its expression is substantially elevated in senescent cells [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were stained according to supplemented manufacturer protocol with the following modification: at the final РВS washing step, the cell nuclei were stained with 1 μg/ml Hoechst 33342 (Molecular Probes, USA). Such modification significantly improves the quality of counting of β-galactosidase negative cells [ 46 ]. The stained cells were visualized using Excitation/Emission Interference Filters (СKX-U: 340-380nm/435-485 nm) on the inverted fluorescent microscope Оlympus СКХ 41 SF (Оlympus, Japan) equipped with Infinity 3-1 (Lumenera Copr., Canada) CCD camera and 20X objective.…”
Section: Methodsmentioning
confidence: 99%
“…Gradual loss of cellular functions including the ability to proliferate with an increase in the number of cell divisions during cell population development was called replicative aging or cellular senescence [ 21 ]. During aging, the cell undergoes substantial changes in functional activity, morphology, and proliferative potential [ 22 , 23 ]. The number of EPCs decreases with aging, along with their ability for proliferation, migration, and angiogenesis [ 24 , 25 ], as we found formerly in senescent EPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this assay being useful for the identification of senescent MSC passages (those containing no colony forming cells), it notably measures highly-proliferative, as opposed to senescent cells, and is time consuming and highly subjective. In a recent study by Zorin et al, the group confirmed that cells that tested positive for senescence were the highest in small diffuse colonies of human skin fibroblast cultures, and they originated from the cells with the least proliferative potential [54]. However, counting such small colonies as representative of pre-senescent cells remains inaccurate and very subjective.…”
Section: Replicative and Stress-induced Senescence In Msc Cultures: Mmentioning
confidence: 99%